1.9 μm laser and visible light emissions in Er3+/Tm3+ co-doped tellurite glass microspheres pumped by a broadband amplified spontaneous emission source. (11th February 2019) - Qin, Jingjing; Huang, Yantang; Liao, Tingdi; Xu, Canhua; Ke, Chaozhen; Duan, Yafan
Abstract: From Er 3+ /Tm 3+ co-doped tellurite glass microspheres, simultaneous laser oscillation at 1.9 μ m, and green and red fluorescence emissions with three photons upconversion luminescence were obtained. The microsphere was pumped by a low-cost 1550 nm broadband amplified spontaneous emission source instead of a bulky and expensive tunable laser. It as a non-polarized light provided a wide wavelength range and the multiple wavelengths resonant absorption was obviously observed from the transmission spectra. The use of broadband source made the entire microsphere laser more adaptively stable to withstand the vibration interference and temperature variations. The coupled threshold power was as low as 1.5 mW. It was demonstrated that the Er 3+ ions acted as sensitizers to efficiently absorb the pump photons and transfer energy to Tm 3+ ions. Therefore, this approach would have potential applications in optical fiber lasers, sensors and lighting devices.